Structural Ordering and Charge Variation Induced by Cation Substitution in (Sr,Ca)AlSiN3:Eu Phosphor - Tsai, Yi-Ting; Chiang, Chang-Yang; Zhou, Wuzong; Lee, Jyh-Fu; Sheu, Hwo-Shuenn; Liu, Ru-Shi (Journal of the American Chemical Society, 2015)
Nitride phosphors are suitable for white light-emitting diode applications. In this study, the structure of phosphor has been modified through cation substitution to induce charge variation and a rearrangement of neighboring nitride clusters, and consequently enhance its luminescent behavior. Substitution of Ca(2+) by Sr(2+) cations expanded the lattice volume and the bc plane, but shortened the distance between the layers along the a axis. Lattice distortion of the framework introduced high-coordination sites in the Sr/Eu centers and adequate space, thereby facilitating charge variation of activators under reduced atmosphere, as detected through X-ray absorption near-edge structure spectroscopy. As such, the photoluminescent intensity of the phosphors increased by more than 10% and a blue shift occurred. The microstructures of the samples were also analyzed using high-resolution transmission electron microscopy. Cation substitution induced a special change in the anion environment, as indicated in the solid-state Raman spectra. Moreover, typical ordering variations in the SiN4 and AlN4 clusters are generated in the lattice. Meanwhile, neighbor sequence of (Si/Al)N4 around the divalent centers were observed through solid-state nuclear magnetic resonance spectroscopy. The modified ordering distribution resulted in a rigid structure and improved the thermal quenching behavior. Thermal stability has been enhanced by 10% at 473 K when x = 0.9 in SrxCa0.993-xAlSiN3:Eu(2+)0.007 compared with that at x = 0. This study promotes the research of neighbor sequence for selective tetrahedral sites such as Li, Mg, Al, and Si coordinated by N atoms in contact with cation sites.